Detection and genotyping of Epstein-Barr virus by polymerase chain reaction in tissues obtained from cases with Hodgkin's disease in Turkey - Durmaz, R; Aydin, A; Köroglu, M; Aker, H; Özercan, IH; Atik, E; Arici, S (Slovak Academic Press Ltd, 1998)
In order to determine the positivity rare and genotype of Epstein-Barr virus (EBV) in cases with Hodgkin's disease (HD) in Turkey, 40 tissue specimens from HD patients were analysed. Ten non-lymphoid tissue samples from individuals without any evidence for lymphoma were used as controls. The cases with HD included 33 males and 7 females with a mean age of 28 years. Nodular sclerosis was the most prevalent histological subtype (16/40) followed by mixed cellularity (10/40), lymphocyte predominance (9/40), and lymphocyte depletion (5/40). After histopathological evaluation, deparafinisation and lysis of the specimens, one-stage polymerase chain reaction (PCR) and two-stage (nested) PCR assays were performed with the primers common for both EBV genotypes and the primers specific for EBV types 1 and 2, respectively. EBV DNA was detected in 22 of 40 (55%) cases with HD and in 1 of 10 (10%) control specimens. The distribution of EBV DNA positivity according to the histological subtypes was as follows: 10 of 16 (62.5%) for nodular sclerosis, 3 of 5 (60%) for lymphocyte depletion, 5 of 9 (55.6%) for lymphocyte predominance, and 4 of 10 (40%) for mixed cellularity. Although most of the HD patients were males of 15 - 34 years of age, there were no significant differences between EBV positivities obtained From different sex and age groups. The rates of EBV genotypes were 82% for type 1, 9% for type 2, and 9% for both types, respectively.
Keywords: Epstein-Barr virus; virus genotype; Hodgkin's disease; polymerase chain reaction